2012
DOI: 10.1371/journal.ppat.1002569
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Virus Respiratory Infection and Transmission Following Ocular Inoculation in Ferrets

Abstract: While influenza viruses are a common respiratory pathogen, sporadic reports of conjunctivitis following human infection demonstrates the ability of this virus to cause disease outside of the respiratory tract. The ocular surface represents both a potential site of virus replication and a portal of entry for establishment of a respiratory infection. However, the properties which govern ocular tropism of influenza viruses, the mechanisms of virus spread from ocular to respiratory tissue, and the potential differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 50 publications
3
89
0
1
Order By: Relevance
“…However, it does not appear that virus replication in ocular tissue is necessary for subsequent respiratory infection, because not all productively infected ferrets had detectable virus in ocular samples (Tables 1 and 2). As in other models of ocular inoculation with influenza viruses (12,24), 100% infectivity of ferrets following OA inoculation was not observed, likely due to low presented doses, ferret-to-ferret physiological differences, or differences in the ocular surface area exposed during OA inoculation. The inclusion of an impinger sampler to measure the presence of aerosolized virus in the secondary chamber represents the most direct and comprehensive method possible to measure potential respiratory exposure during ocular-only inoculation; the absence of aerosolized virus outside the goggles during the inoculation and the lack of detection of virus in conjunctival wash specimens on day 1 p.i.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…However, it does not appear that virus replication in ocular tissue is necessary for subsequent respiratory infection, because not all productively infected ferrets had detectable virus in ocular samples (Tables 1 and 2). As in other models of ocular inoculation with influenza viruses (12,24), 100% infectivity of ferrets following OA inoculation was not observed, likely due to low presented doses, ferret-to-ferret physiological differences, or differences in the ocular surface area exposed during OA inoculation. The inclusion of an impinger sampler to measure the presence of aerosolized virus in the secondary chamber represents the most direct and comprehensive method possible to measure potential respiratory exposure during ocular-only inoculation; the absence of aerosolized virus outside the goggles during the inoculation and the lack of detection of virus in conjunctival wash specimens on day 1 p.i.…”
Section: Discussionmentioning
confidence: 53%
“…route suggest a potential mechanism for the reduced frequency of virus transmission observed in these studies (26). Accordingly, a decreased incidence of sneezing and nasal discharge was detected among ferrets inoculated by the ocular route (either with a liquid inoculum or by OA inoculation) (12), which could contribute to reduced transmissibility. Further study is needed to better understand the dissemination of virus from ocular tissues and the contribution this may make to virus transmission.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Although a recent study showed H5N1 virus infection of ciliary process epithelial cells in ferrets, the permissiveness of human uveal cells to influenza virus infection and sialic-acid receptor expression patterns remain in question [2,43]. By analyzing the permissiveness to influenza A/H1N1pdm virus and sialic-acid receptor expression patterns of this panel of human neuronal and ocular cells in vitro, this study contributes to knowledge concerning neurological and ocular complications of influenza and possibly other viruses.…”
Section: Introductionmentioning
confidence: 95%